Contrast-enhanced ultrasound evaluation of placental perfusion in brachicephalic bitches - Silva, Priscila [UNESP]; Maronezi, Marjury Cristina [UNESP]; Padilha-Nakaghi, Luciana Cristina [UNESP]; Gasser, Beatriz [UNESP]; Pavan, Letícia; Nogueira Aires, Luiz Paulo [UNESP]; Russo, Marco; Spada, Stefano; Ramirez Uscategui, Ricardo Andrés; Moraes, Paola Castro [UNESP]; Rossi Feliciano, Marcus Antônio [UNESP] (Elsevier, 2021)
The present study aimed to investigate placental hemodynamics to determine quantitative and qualitative parameters for pregnant brachycephalic bitches as well as describe placental vascularization and perfusion in females with fetal abnormalities close to delivery. Forty-four healthy fetuses from 22 brachycephalic bitches and 9 fetuses with gestational abnormalities (anasarca and hydrocephalus) from 8 brachycephalic bitches were evaluated. All female dogs were artificially inseminated intravaginally and underwent cesarean section at the end of gestation. Pregnancy diagnosis was made on the 25th day and experimental evaluations were performed on Days 25 (M1), 45 (M2), and 58 (M3) of gestation in normal pregnancies. Fetuses with gestational abnormalities were evaluated at the last time point. Biometric values of the fetuses were determined by B-mode and vascular indices by Doppler fluxometry of the umbilical artery, whereas qualitative assessment of contrast filling and quantitative parameters of placental perfusion were performed using CEUS. Parameter comparisons among the examined fetuses (normal and abnormal) and between the moments (M1, M2, and M3) were performed by Student's t-test and ANOVA tests, and then correlated using the Spearman test. In healthy fetuses, systolic and diastolic velocities as well as the time averages of minimum and maximum velocities increased significantly from M2 to M3 (P < 0.05), whereas the pulsatility index (P < 0.043) and vascular resistance (P < 0.001) decreased. Contrast distribution was always homogeneous in placental tissues and CEUS filling parameters remained constant during the evaluated periods (P < 0.05). In fetuses with hydrops, Doppler values were similar to those obtained in healthy subjects (P > 0.05), but CEUS evaluation demonstrated a heterogeneous distribution with lower intensity of placental tissue filling and a delay in perfusion time (P < 0.05) with a diagnostic accuracy of 75%. The association of dopplerfluxometry and CEUS allowed evaluation of qualitative and quantitative parameters of physiological pregnancy hemodynamics in all gestational thirds without evidence of significant changes in the physiology of the maternal-fetal binomial, and CEUS was shown to be applicable in the detection of failures in placental vascular filling (tissue dysfunction) in fetuses with anasarca and hydrocephaly.
Keywords: Canines; CEUS; Gestational abnormalities; Placental perfusion